Effect of Chewing Gum on Thirst in Kidney Failure Patients: Review - Loritta Yemina; Santa Maria Pangaribuan; Samsinar Butar-butar (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims:  Complaints of thirst accompanied by dry mouth are the main complaints of hemodialysis patients with poor compliance due to excess fluid intake, inability to restrict fluids, and high interdialytic weight. The interventions carried out to overcome thirst include sucking ice cubes, gargling with boiled water, and chewing gum. The effectiveness of chewing gum for people with CKD is still debated. Objectives: The purpose of this study was to determine the benefits of chewing gum in overcoming thirst in CKD patients on hemodialysis. Methods: The electronic databases used in this research are PubMed, ProQuest, MEDLINE (EBSCO), and Google Scholar. A search for reading materials was carried out to identify discussions that fit the inclusion criteria. The keywords used were "chewing gum", "hemodialysis," and "thirst." Results: We found 2350 articles based on the keyword, and seven articles meet the inclusion criteria after going through a series of article selection actions. Conclusions: This review recommended chewing gum as an alternative therapy for overcoming the thirst of kidney failure patients.